Downer reactor simulation and its application on coal pyrolysis: A review - Xueer Pan; Wenhao Lian; Jingxuan Yang; Junli Wang; Zhonglin Zhang; Xiaogang Hao; Abuliti Abudula; Guoqing Guan (Carbon Resources Conversion, 2022)
Pyrolysis technology has received increasing attention in recent years due to its great potential in the field of low-rank coal clean and efficient conversion. Since pyrolysis reaction is very fast and prone to overreaction, the downer-type reactor is considered as a pyrolyzer due to its unique plug flow reactor characteristics. However, the low solids holdup, which is not beneficial for the fast heat transfer, limits its industrial application. Thus, how to realize high-density operation is crucial to the successful application of the downer reactor. Herein, the definition and strategies of high-density operation in the downer were introduced at first. And then, considering the increasing influence of computational fluid dynamics (CFD) in the fluidization industry, the state-of-the-art progress in downer simulation was reviewed, in which the newly developed drag models for downers were carefully discussed and compared. Also, to help prediction of the pyrolysis behaviors, the widely used pyrolysis kinetic models were systematically summarized. Combined with the potential of the downer in the field of coal pyrolysis, the relevant research progress of hot-state simulation of the downer pyrolyzer were introduced and analyzed. Finally, the suggestions on how to carry out follow-up work were given. It is expected that this review could give a better understanding for designing and optimizing downer pyrolyzer.